PENGARUH PENDIDIKAN KESEHATAN PENYAKIT JANTUNG KORONER TERHADAP SIKAP DAN MOTIVASI BERHENTI MEROKOK - Diyono, Diyono; Setiani, Ditya Yankusuma (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. The prevalence of smokers in Indonesia tends to increase reaching 62.9% in men and 4.8% in woman. That is need more effective efforts to be sought to reduce the prevalence of smokers.The Aim of the Study. To know the effect of health education about coronary heart disease on smoking attitudes and motivation to quit smoking.Subject and Method. Quasi experiment research by pre post design. A sample of 42 smokers was taken by simple random sampling. Data were analyzed by Paired t-test.Results. (1) The average value of smoking cessation attitude increased from 28.7 to 31.1; p = 0.019. (2) The average value of quitting smoking motivation increased from 12.1 to 16.7; p = 0.000.Conclusion. Coronary heart disease education is effective in improving attitude and motivation to stop smoking.Keywords: attitudes, health education, motivation, quit smokingKorespondensi: Diyono. AKPER PANTI KOSALA SURAKARTA. Jalan Raya Solo - Baki Km. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: dionsanfizio@gmail.com